2019
DOI: 10.21873/anticanres.13256
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Outcomes of Surgical Treatment for Remnant Gastric Cancer After Distal Gastrectomy

Abstract: Background/Aim: Remnant gastric cancer (RGC) after distal gastrectomy occurs in 1-2% of patients, while the biological features of RGC are unknown. Patients and Methods: A total of 22 consecutive patients with RGC who underwent total gastrectomy were analyzed. Their disease history included either gastric cancer (n=16) or peptic ulcer (n=6). Overall, 18 underwent open total gastrectomy (OTG) and 4 underwent laparoscopic total gastrectomy (LTG). Results: The mean number of lymph nodes dissected and metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Many surgeons have successfully applied LCTG, and this technique is considered the preferred treatment option (Table 5) [24][25][26][27][28][29][30][31][32][33]. As shown in Table 6, our results are consistent with those of comparative studies [14][15][16][17][18][19][20][21]. The patients in the LCTG group had smaller tumor size, lower numbers of metastatic lymph nodes, and lower pathological stages than patients in the OCTG group; however, the clinical stage distribution, dissection, and retrieved lymph nodes showed no signi cant differences between the groups.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Many surgeons have successfully applied LCTG, and this technique is considered the preferred treatment option (Table 5) [24][25][26][27][28][29][30][31][32][33]. As shown in Table 6, our results are consistent with those of comparative studies [14][15][16][17][18][19][20][21]. The patients in the LCTG group had smaller tumor size, lower numbers of metastatic lymph nodes, and lower pathological stages than patients in the OCTG group; however, the clinical stage distribution, dissection, and retrieved lymph nodes showed no signi cant differences between the groups.…”
Section: Discussionsupporting
confidence: 85%
“…The patients in the LCTG group had smaller tumor size, lower numbers of metastatic lymph nodes, and lower pathological stages than patients in the OCTG group; however, the clinical stage distribution, dissection, and retrieved lymph nodes showed no signi cant differences between the groups. Additionally, the number of retrieved lymph nodes was equal to that reported in other studies (Table 6) [14][15][16][17][18][19][20][21]. The OCTG group had a higher number of recurrences and deaths than the LCTG group, because the OCTG group had more advanced cases, leading to a worse 5-year overall survival rate than the LCTG group.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…After distal gastrectomy, Billroth II reconstruction is the most common reconstruction performed worldwide. In the past, the number of gastric resections, especially for benign pathologies such as gastric ulcers, was higher, so today, we can observe a certain number of gastric carcinoma arising at the anastomotic site, that is, gastric stump cancer [1,2]. The case reported in this article demonstrates the use of minimally invasive technology to remove a remnant stomach that is tenaciously embedded by adhesions and how to perform the reconstruction of the digestive tract.…”
Section: Introductionmentioning
confidence: 85%
“…In terms of the postoperative complication rate, five of the ten studies reported a 6.5%–23.3% risk reduction with LG compared to that of OG[60,62,64,65,68]. The remaining five studies showed unfavorable results from the laparoscopic approach in terms of the postoperative mortality rate, although the result was not statistically significant[61,63,66,67,69]. LG was also associated with a significantly shorter postoperative hospital stay than OG, as shown in one of the non-RCTs.…”
Section: Laparoscopic Gastrectomy For Remnant Gastric Cancermentioning
confidence: 99%